Like Animals Like Human Beings: An Ecocritical Metaphor Discourse of Leadership in Selected Poems of Niyi Osundare - Festus Moses Onipede; Gabriel Abiodun Abioye (JURNAL ARBITRER, 2023)
Niyi Osundare extensively investigates the natural world, which is the habitat inhabited by nonhuman beings, in his poems. As a result, his poetry is referred to as eco-poetry. There have been a lot of studies of Niyi Osundare’s poetry that have focused on traditional aesthetics, political power, exile, and the African experience, but not enough studies that have looked at the leadership of animals in their natural habitats. The main sources of information for the study are Niyi Osundare’s The Leader and the Led and Random Blues. This study examined the animal metaphor in relation to leadership from the viewpoints of Lakoff and Johnson’s conceptual metaphor theory and Michael Halliday’s transitivity theory. Four main participant and process categories are identified by the data as being present in the poems, with the Material and Relational processes having the largest frequency distributions (62.98% and 22.22%, respectively). This large proportion indicates both the ongoing activity in the African continent and the significant demands that people are under in their desire to rule the biosphere. The the low occurrence of verbal and mental processes in followers (11.11% and 7.40%, respectively) suggests that both animal and human leadership aspirants are more interested in what followers do than followers are. Also, the findings revealed the metaphorical representation of each animal thus: serpent(complacence), leeches and lice (parasite), orangutans (class), beasts (hard labor), crocodile (betrayal), hive (defense), lion (subjugation), antelopes/impalas (fright), hyena (glutton), giraffe (nonchalance), zebra (duplicity), elephant (destruction), warthog (ugliness), rhino (violence), snake (anarchy), lamb (peace), tiger (aggression), doe (compassion). Overall, the study concluded that we need leaders and followers who are similar to lambs and does for harmonious cohabitation in the ecosystem.